The way we're working isn't working : the four forgotten needs that energize great performance - Schwartz, Tony, 1952-; Gomes, Jean.; McCarthy, Catherine, 1968- (New York : Free Press, 2010)
Drawing on extensive work with an extra-ordinary range of organizations, among them Google, Ford, Sony, Ernst & Young, Shell, IBM, the Los Angeles Police Department, and the Cleveland Clinic, Schwartz creates a road map for a new way of working that focuses on four core needs that energize great performance: sustainability, security, self-expression, and significance.
Includes bibliographical references (p. [297]-315) and index.
Keywords: Performance; Work -- Psychological aspects; Organizational effectiveness; Personnel management